Two new species of Cephalogonimidae Looss, 1899 (Digenea: Plagiorchioidea) from Africa (Mozambique and Guinea), including a new phylogenetic hypothesis for related plagiorchioids. (April 2021) - Curran, Stephen S.; Dutton, Haley R.; Warren, Micah B.; du Preez, Louis; Bullard, Stephen A.
Abstract: Two new species of Cephalogonimidae Looss, 1899 (from Emoleptalea Looss, 1900 and Masenia Chatterji, 1933) are described from African freshwater fishes. Emoleptalea mozambiquensis n. sp. infected the turquoise killifish, Nothobranchius furzeri Jubb, in Mozambique and differs from its nine congeners by the combination of differences in body shape and size, oral sucker shape, sucker width ratio, configuration of the digestive tract and gonads, vitelline follicle shape and vitellarium configuration. Emoleptalea dollfusi Srivastava, 1960 is a synonym of Emoleptalea loossi Srivastava, 1960, thus there are still nine accepted species. Masenia baroensis n. sp. infected the globe fish, Tetraodon lineatus L., in the Republic of Guinea and differs from its five African congeners and 15 Asian congeners by the combination of circumoral spine count, oral sucker shape, caecal extent, ovary shape, genital pore position, and configuration of the vitellarium. Masenia dayali (Gupta & Puri, 1984) Chandra & Saxena, 2016 and Masenia pushpanjalii are nomina dubia . We propose Masenia ritai (Agrawal, 1964) n. comb., with M . ritai Sircar & Sinha, 1970 its junior synonym. Heterorchis cf. crumenifer (identified tentatively due to egg size) is reported from the West African lungfish, Protopterus annectens (Owen), in Mozambique (new geographical record). Heterorchis protopteri Thomas, 1958 and Heterorchis ghanensis Thomas, 1968 are species inquirendae . Sequences (28S rDNA) from these parasites were included in a Bayesian phylogenetic analysis with 37 other ingroup taxa. Both new species formed a clade with Masenia nkomatiensis Dumbo, Dos Santos & Avenant-Oldewage, 2019 from Africa. These three species formed a sister relationship with the other available cephalogonimids: Cephalogonimus americanus Stafford, 1902 and Cephalogonimus retusus (Dujardin, 1845), both frog parasites from North America and Europe, respectively. Heterorchis cf. crumenifer represented a distinct lineage within the Plagiorchioidea but formed a polytomy with species from 10 plagiorchioid families. Graphical abstract: Image 1 Highlights: Two new species in Cephalogonimidae, Emoleptalea mozambiquensis and Masenia baroensis . Large subunit ribosomal DNA based phylogeny unites the new species as close relatives. Affinity of Heterorchis with the Plagiorchioidea is demonstrated in the phylogeny. Family group name for Heterorchis remains enigmatic.